2000
DOI: 10.1046/j.1439-0264.2000.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Position and Histological Structure of the Testes in the Brown Hare (Lepus europaeus) during Seasonal Regression and Recrudescence

Abstract: The position and histological structure of the testes of 33 brown hares (Lepus europaeus) were studied from July to December. From July to September, the testes were located in the scrotum; in October and November, in some animals, the testes were positioned more or less in the inguinal canal towards the abdominal cavity, and in December none of the investigated animals had testes located in the scrotum. Testes were weighed and a quantitative analysis of tissue components was performed: the diameter of the sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
4
7
0
Order By: Relevance
“…The birth weight of L. europaeus is approximately 100 g (Macdonald and Barrett, 1993). In this study, four fully furred fetuses of a doe were obtained from Central Anatolia in August, and their body weights were 93, 97, 99, and 106 g. Additionally, the seasonal changes in testicle position of the European hares in our study were consistent with findings given by Simeunovic et al (2000). The breeding seasons and mean litter sizes of European hares from various countries around the world are presented in the Table. The sex ratio for hares is subject to fluctuation and is sometimes in favor of females and sometimes males.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The birth weight of L. europaeus is approximately 100 g (Macdonald and Barrett, 1993). In this study, four fully furred fetuses of a doe were obtained from Central Anatolia in August, and their body weights were 93, 97, 99, and 106 g. Additionally, the seasonal changes in testicle position of the European hares in our study were consistent with findings given by Simeunovic et al (2000). The breeding seasons and mean litter sizes of European hares from various countries around the world are presented in the Table. The sex ratio for hares is subject to fluctuation and is sometimes in favor of females and sometimes males.…”
supporting
confidence: 86%
“…However, Hackländer et al (2011) revealed that the reproductive pattern of European hares is affected by actual winter temperatures regardless of latitude, and hence, European hares in regions with mean annual temperatures above 0 °C breed throughout the year. Simeunovic et al (2000) discussed the change in the testicle position of European hares in Slovakia by month.…”
mentioning
confidence: 99%
“…Apoptotic bodies are cleared by Sertoli cells, but some of the dying cells and apoptotic bodies get detached and can be seen in the epidydimis. Absence of TUNEL positive Leydig cells can be explained with observations that there is only the decrease in volume, but not in the number of Leydig cells in regressing hamster testis [5]. We can establish an inverse correlation between apoptosis and germ cell proliferation.…”
Section: Discussionsupporting
confidence: 50%
“…One of them involves a reduction in spermatogenesis, whereas all the germ cell lines remain present, as in ram (Hochereau-de Reviers et al, 1985, 1992, deer (Hochereau-de Reviers & Lincoln, 1978), stallion (Berndtson et al, 1983) and mole rat (Gottreich et al, 1995). Another strategy is spermatogenesis arrest, when tubular sections with spermatogonia and spermatocytes can be observed microscopically, as in deer (Sch€ on et al, 2004), black bear (Tsubota et al, 1997), bank vole (T€ ahk€ a et al, 1997), prairie dog (Foreman, 1997) ( Barnes et al, 1986), or brown hare (Simeunovic et al, 2000). Finally, a third strategy is the much earlier arrest of spermatogenesis, when tubular sections with only spermatogonia and Sertoli cells are observed, as with the hairy armadillo (Luaces et al, 2013), mink (Pelletier, 1986;Blottner et al, 2006) or yellowish myotis (Ara ujo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the length of the seminiferous tubule decreased sharply only between MR and SR groups. In animals in which tubular sections have been observed in spermatocyte arrest, as in Syrian hamster, only parameters such as tubular thickness (Simeunovic et al, 2000) or variations in the epithelial, tubular, and interstitial areas (Velez et al, 2010) have been studied, although semiquantitatively. All this also applies to mammals and birds in which epithelial atrophy is stronger (Pelletier, 1986;Madekurozwa et al, 2002;Sch€ on et al, 2004;Blottner et al, 2006;Islam et al, 2010;Ara ujo et al, 2013;Luaces et al, 2013).…”
Section: Discussionmentioning
confidence: 99%